Perilaku Anak Jalanan dan Strategi Pengentasannya di Bandung, Bogor, dan Jakarta - Sri Tjahjorini; Sumardjo Sumardjo; Margono Slamet; Djoko Susanto; Darwis S Gani (Jurnal Penyuluhan, 2009)
Street child problems, like iceberge phenomenon, of which the regional pockets, the distribution and the age tremendously increase day by day. Since 1997 the government of Indonesia through the Social Ministry has been carrying out efforts to overcome the problems, but up to now the efforts have not yielded the expected results because of the limited information of the problems. The present research was addressed to provide informations on the phenomenon profiles of street children and strategies for their elimination in Bandung, Bogor and Jakarta. Data were collected using structured interviews, focus group discussion and direct observation. The collected data were analysed using parametric and non-parametric statistics. Population were street children, 5-21 years of age. Sample in each region was consisted of 75 persons, 50 males and 25 famales, drawn using cluster random sampling  technique, and 25 parents of  the respondens as a cross check. The influence of family background on the street children behavior, direct or indirectly, was more obvious compared to that of  environmental background. The latter was indirect through sociologic characteristics of the street children particularly on the non formal education. Strategy for elimination of the street children could be equally applied for the whole regions, except for its approach, which can use the TRIBINA, which means  Human Building, Environmental Building and Efforts Building could be employed.